The Changing Story digital stories that participate in transforming teaching & learning - Buturian, Linda (Open textbook library., 2016)
The Changing Story gives you assignments, resources, and examples to use in your teaching and learning. It will also help you think of ways digital stories can be used in your teaching, and help students harness the power of visual storytelling.